Grim consequences of workplace traditional bullying and cyberbullying by way of mediation: A case of service sector of Pakistan - Iftikhar, Mehwish; Beh, Loo See (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Various studies have been conducted to measure bullying incidence and prevalence in multiple organizational settings based on a variety of methods and research design. Nonetheless, these studies indicate that bullying is a devastating and crippling problem that should be addressed in relation to its adverse effects and implications. This study identified several gaps in the literature when expanded specifically to the service sector of Pakistan, where the problem of bullying is prevalent. This research endeavored to fill in the aforementioned gaps by precisely focusing on organizational climate as a cause of bullying (based on frustration–aggression theory and social interaction approach), technology in relation to cyberbullying, and effects on employee health. Hence, this study contributes to the emergent discussion in identifying the debilitating outcomes of bullying. Results indicated the significant negative relationship of organizational climate and workplace bullying and the grim consequences on employees' health in the form of psychological, physiological, and emotional health distractions. © 2019, Blue Eyes Intelligence Engineering and Sciences Publication. All rights reserved.